Tower dungeon. 2 - Nihei, Tsutomu, 1971- (Kodansha USA, 2025)
Eriquo, Lillicen, and Yuva are left to rescue the princess on their own after their commanding officer, who just so happens to be the king's sister, is whisked back to the capital to sit the throne in his absence. The three face innumerable dangers as they begin to tease out the secrets of the Dragon Tower--but danger lurks without as well as within. Haughty knights, mighty sorcerers, a killer with the indomitable power of the Dracomorph...Monsters come in many forms!